How to expand a vintage men’S grooming brand worldwide? the case of musgo real from Claus Porto/Ach Brito - Lourenço, Maria João Custódio (2018)
Nowadays, wearing a beard and/or moustache is common and it is considered trendy – we are actually facing a “peak beard”. Bearded men adopt specific products for functional reasons. Additionally, men are increasingly involved in the purchasing decision process, looking for a store experience around their interests in sync with their styling interests, and then buying their own men’s grooming products. Within this context, the present work project aims to study how to expand the vintage men’s grooming brand Musgo Real worldwide. In order to address the above mentioned objective, an exploratory research was conducted (qualitative interviews) followed by a quantitative survey to test the hypothesis inferred from the qualitative research. The main findings are: 1) Musgo Real is considered a high-quality, aesthetic and premium grooming brand exclusively for men; 2) However, the brand is lacking awareness. 3) Bearded men do not feel that the brand is targeting them. 4) On the other hand, we consider that Musgo Real has the potential to enter successfully into the beard care segment. Specific recommendations to achieve this goal are presented in this work project.